IMPROVING THE STUDENTS’ READING SKILL THROUGH DOUBLE BRAIN POWER METHOD’ AT THE SECOND GRADE STUDENTS’ OF SMA YPPP WONOMULYO - Cici Musyahrafa; Nurdevi Bte Abdul; Wildhan Burhanuddin (FKIP Unismuh Makassar, 2021)
This research aimed to finding out whether or not the use of Double Brain Power Method in improving the reading skill. The research in terms of finding the student that focus on level of literal and interpretative the improvement of students’ ability by using Improving The Students’ Reading Skill Through Double Brain Power Method’ at the second grade students’ of SMA YPPP Wonomulyo.The research used Classroom Action Research (CAR) as the method of the research. The researcher conducted two cycles, where each cycle consisted of four meetings. The researcher did the classroom action research at class XI IPA 2 of SMA YPPP Wonomulyo. The subjects of this research were 30 students. The research findings showed that second grade students’ in SMA YPPP Wonomulyo was improvement from cycle I to cycle II. The students’ improvement in literal comprehension through Double Brain Power Method It indicated that there was significant improvement of the students’ reading comprehension from the diagnostic test to cycle I and cycle II, where in the diagnostic test the students’ mean score was 4.55, but after the evaluation test in cycle I, it was become 6.03. So the improvement of the students’ achievement from diagnostic test to cycle I was 34.15. There was also significant improve from cycle I to cycle II where the students’ mean score in cycle II was 8.53. The improvement of the students’ mean score from cycle I to cycle II was 41.46. From these findings, the researcher made conclusion that by using double brain power method could improve the students’ reading skills achievement and make the students’ active in learning process.